Broadband access technologies evaluation tool (BATET) - Pereira, João Paulo (2008)
The goal of this paper is to identify all the essential costs of building broadband access networks, and then to perform a comparison of different technologies in various scenarios. Different market segments (Scenarios) have different geographical characteristics and will require different amounts of access bandwidth. These different market segments will be served by alternative access technologies that minimize overall costs. In order to do this, we have developed a model framework and a evaluation tool. To measure the attractiveness of the several broadband access technologies, the proposal tool compares the costs, revenues, NPV, IRR, payback periods, etc. for three scenarios. The paper presents a techno-economic analysis of eight broadband technologies for access networks: digital subscriber line (DSL), hybrid fiber coax (HFC), power line communications (PLC), fiber to the home (FTTH), fiber to the curb (FTTC), fiber to the cabinet (FTTCab), and wireless alternatives such as WiMAX and satellite.